Beyond Transactions: How Relational Capital Drives Brand Loyalty in Bali’s Tourism SMEs - Diwyani, Ni Made Sthita Prajnasya; Agustina, Ni Ketut Wiwiek (Journal of Business on Hospitality and Tourism, 2025)
In the post-pandemic tourism landscape, travel agencies must rebuild customer loyalty through relational strategies. This study examines the direct effects of customer engagement and brand trust on brand loyalty among 289 customers of a Bali-based travel agency. Using multiple linear regression in SPSS 25, findings confirm that both customer engagement (β = 0.396, p < 0.001) and brand trust (β = 0.453, p < 0.001) significantly and positively influence brand loyalty, with the model explaining 68% of variance (R² = 0.680). Simultaneously, the two predictors exert a strong joint effect (F = 303.306, p < 0.001). The results affirm that even in an era of digital self-booking, interpersonal trust and emotional engagement remain critical drivers of loyalty in tourism intermediaries. Strategic recommendations include investing in personalized communication, transparent service recovery, and consistent brand delivery to strengthen relational equity.